2006
DOI: 10.1002/adsc.200600343
|View full text |Cite
|
Sign up to set email alerts
|

Lewis Acid‐Catalyzed Sequential Transformations: Straightforward Preparation of Functional Dihydropyridines

Abstract: Lewis acids catalyze the addition of b-enaminoacrylates or b-enaminones to a,b-unsaturated aldehydes leading to substituted dihydropyridines in high yields under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Moderate to excellent yields have been obtained by performing the reactions in a stepwise manner (Scheme 3). 11 Later on, the one step, three-component reaction of a 1,3-dicarbonyl compound, primary amine and a,b-unsaturated aldehyde has been realized by Menéndez and coworkers. Their method was established by employing cerium ammonium nitrate (CAN) as a Lewis acid catalyst.…”
Section: Introductionmentioning
confidence: 98%
“…Moderate to excellent yields have been obtained by performing the reactions in a stepwise manner (Scheme 3). 11 Later on, the one step, three-component reaction of a 1,3-dicarbonyl compound, primary amine and a,b-unsaturated aldehyde has been realized by Menéndez and coworkers. Their method was established by employing cerium ammonium nitrate (CAN) as a Lewis acid catalyst.…”
Section: Introductionmentioning
confidence: 98%
“…[8] Several studies have shown that enamines bearing a secondary nitrogen atom react with electrophiles preferably at the nucleophilic enamine carbon atom, and that strong electrophiles such as acid chlorides or iso(thio)cyanates are required. [9] Therefore, the reaction with acetonitrile as a rather weak electrophile was unexpected and worth exploration. Moreover, the oxidative formation of NÀN bonds is rare in organic synthesis, often being limited to intramolecular reactions and mostly promoted by strong oxidants like hypervalent iodine(III) reagents.…”
mentioning
confidence: 98%
“…Hantzsch DHP synthesis is one of the most broadly used methods for the preparation of DHPs. In order to improve the efficiency of Hantzsch DHPs synthesis, different catalysts have been explored, and many of them exhibited excellent catalytic activity , such as L‐proline , S‐Valin , Yb(OTf) 3 , molecular I 2 , TBAHS , HOAc , Et 3 N , DBU , Py , ceric ammonium nitrate (CAN) , and so on. These methods, however, suffer from drawbacks such as the use of expensive catalysts, difficulty in availability or preparing the starting materials or catalysts, the environmental pollution caused by utilization of solvents and homogeneous catalysts, low yields, long reaction times, tedious work‐up, waste control, and formation of side products.…”
Section: Resultsmentioning
confidence: 99%